Influence of Magnitude and Duration of Altered Gravity and Readaptation to 1 g on the Structure and Function of the Utricle in Toadfish, Opsanus tau - Boyle, Richard; Popova, Yekaterina; Varelas, Joseph (Frontiers in Physiology, 2018)
Gravity has remained constant during animal evolution and the neural sensory systems detecting acceleration forces have remained remarkably conserved among vertebrates. The utricular organ senses the sum of inertial force due to head translation and head tilt relative to gravitational vertical. Change in gravitational force would be expected to have profound effects on how an organism maintains equilibrium. We characterize the physiology of utricular afferents to applied accelerations in the oyster toadfish, Opsanus tau, in normal 1g to establish benchmarks, after 1-32 day exposures to 2.24g (resultant) via centrifugation (hypergravity, HG), after 4- and 16-day exposures to 1.12g (resultant), and following 1-8 days recovery to HG exposures to study re-adaptation to 1g. Afferents were also examined during activation of efferent vestibular pathway. Centrifugation at 2.24 g included 228°/s constant angular velocity component, and thus horizontal canal afferent responses to yaw rotation were recorded as an internal control in each fish. Afferents studied after 228°/s rotation for 4 and 16 days without centripetal acceleration, called On-Center-Control, were indistinguishable from their control counterparts. Principal response to HG was an adjustment of afferent sensitivity as a function of magnitude and duration of exposure: an initial robust increase at 3-4 days followed by a significant decrease from 16-32 days. Initial increase observed after 4 days of HG took >4 days in 1g to recover, and the decrease observed after 16 days of HG took >2 days to readapt to 1g. Hair cells in striola and medial extrastriola macula regions were serially reconstructed in 3D from thin sections using transmission electron microscopy in control fish and fish exposed to 4- and 16-days of HG. Despite the highly significant differences in afferent physiology, synaptic body counts quantified in the same fish were equivalent in their inter-animal variability and averages. No clear role of the efferent pathway as a feedback mechanism regulating afferent behavior to HG was found. Transfer from 1g to HG imparts profound effects on gravitational sensitivity of utricular afferents and the accompanying transfer from the HG back to the 1g resembles in part (as an analog) the transfer from 1g to the µg.